2013
DOI: 10.1590/s1676-06032013000400016
|View full text |Cite
|
Sign up to set email alerts
|

Protozooplankton and its relationship with environmental conditions in 13 water bodies of the Mogi-Guaçu basin - SP, Brazil

Abstract: Protozooplankton is an important component of the aquatic microbial food webs and its composition, density, and distribution reflect the chemical, physical, and biological aspects of the environment. Considering the scarce literature on freshwater protozoans in Brazil and on protozoan ecology in subtropical environments, we listed the ciliates and amoebae taxa found in 13 water bodies in São Paulo State and analyzed their abundance in relation to the environmental variables. We collected two samples in each en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Jack demonstrated that suspended particles can affect the competition of animals by inhibiting the growth of animals such as copepods [48]. In addition, the correlation analysis between eukaryote community structure and environmental factors showed that nitrite concentration also had a significant impact on the eukaryote community structure in the hole, similar to the findings of studies in a deep artificial lake and the Mogi-Guaçu basin [49,50].…”
Section: Discussionsupporting
confidence: 63%
“…Jack demonstrated that suspended particles can affect the competition of animals by inhibiting the growth of animals such as copepods [48]. In addition, the correlation analysis between eukaryote community structure and environmental factors showed that nitrite concentration also had a significant impact on the eukaryote community structure in the hole, similar to the findings of studies in a deep artificial lake and the Mogi-Guaçu basin [49,50].…”
Section: Discussionsupporting
confidence: 63%
“…Although no ciliate species have been identified as constant, some of them were considered accessories, from which we highlight Cinetochilum margaritaceum and Cyclidium glaucoma, who have been registered as frequent and abundant taxa in many rivers and streams (Madoni and Braghiroli, 2007;Bagatini et al, 2013;Segovia et al, 2016). These species, belonging to the order Philasterida, are registered mainly in mesotrophic and eutrophic environments (Beaver and Crisman, 1989), which are the predominant conditions of the Mandacaru stream.…”
Section: Composition and Richness Of Testate Amoebae And Ciliatesmentioning
confidence: 98%
“…The wheat media was prepared, providing a nutritive medium for protozooplankton to accelerate the growth rate. Samples were fixed with mercuric chloride and stained with bromophenol blue for examination and enumeration (Bagatini, et al, 2013). The total count of each protozooplankton species was detected and recorded according to the identification keys of Patterson and Hedley (1996).…”
Section: Water Protozooplankton Examinationmentioning
confidence: 99%
“…Therefore, they can act as natural bio-control in complex ecological systems (Syed et al, 2019). Protozooplankton is an important component of the aquatic microbial food webs and its composition, density, and distribution that reflect the chemical, physical, and biological aspects of the environment (Bagatini, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%